EARLY FERTILIZATION DURING WINTER CULTIVATION AND ITS RESIDUAL EFFECT ON SILAGE MAIZE GROWN SEQUENTIALLY - Bertolino, Karina Mendes; Barbosa Duarte, Giuliana Rayane; Dias Martins, Fábio Aurélio; Fernandes Fonseca, Kamilly Maria; Ribeiro, Elias Costa; da Silva, Edipo Menezes; Silva Botelho, Flávia Barbosa (REVISTA BRASILEIRA DE MILHO E SORGO, 2023)
The objective of this study was to evaluate the effect of an early application of potassium (K) fertilizer on pearl millet (Pennisetum glaucum L.) grown during fall/winter on the performance of maize (Zea mays L.) silage grown in succession. Using a randomized block design, in the fall/winter harvest, the plots were composed of millet and six doses of K (0, 30, 60, 90, 120 and 150 kg K2O ha-1) as muriate of potash (57% K2O) in addition to fallow. In the summer harvest, during the cultivation of maize, six doses of K2O were applied complementary to the doses applied in the autumn/winter harvest to total 120 kg K2O ha-1 (120, 90, 60, 30, 0) and 0 kg K2O ha-1 for the no cover treatment. An additional treatment that was planted to received the recommended fertilization amount (60 and 90 kg ha-1 of K2O for planting and broadcasting, respectively). For the millet, was evaluated plant height, green and dry biomass yields, and soil cover at 30, 60, 90 and 120 days after harvest . For maize, agronomic traits, leaf nutrient content and green and dry biomass yields were evaluated. The early application of K fertilizer did not alter the yield components of millet and silage maize. However, the straw produced by the millet was efficient at promoting soil cover in the off-season.